Using CO line ratios to trace the physical properties of molecular clouds - Peñaloza, Camilo H.; Glover, Simon; Shetty, Rahul; Klessen, Ralf S. (Arxiv, 2016)
The carbon monoxide (CO) rotational transition lines are the most common tracers of molecular gas within giant molecular clouds (MCs). We study the ratio ($R_{2-1/1-0}$) between CO's first two emission lines and examine what information it provides about the physical properties of the cloud. To study $R_{2-1/1-0}$ we perform smooth particle hydrodynamic simulations with time dependent chemistry (using GADGET-2), along with post-process radiative transfer calculations on an adaptive grid (using RADMC-3D) to create synthetic emission maps of a MC. $R_{2-1/1-0}$ has a bimodal distribution that is a consequence of the excitation properties of each line, given that $J=1$ reaches local thermal equilibrium (LTE) while $J=2$ is still sub-thermally excited in the considered clouds. The bimodality of $R_{2-1/1-0}$ serves as a tracer of the physical properties of different regions of the cloud and it helps constrain local temperatures, densities and opacities. Additionally this bimodal structure shows an important portion of the CO emission comes from diffuse regions of the cloud, suggesting that the commonly used conversion factor of $R_{2-1/1-0}\sim 0.7$ between both lines may need to be studied further.